Association of polymorphisms in drug transporter genes (SLCO1B1 and SLC10A1) and anti-tuberculosis drug-induced hepatotoxicity in a Chinese cohort. Issue 1 (January 2015) - Chen, Ru; Wang, Jing; Tang, Shaowen; Zhang, Yuan; Lv, Xiaozhen; Wu, Shanshan; Xia, Yinyin; Deng, Peiyuan; Ma, Yu; Tu, Dehua; Chen, Dafang; Zhan, Siyan
Summary: This study investigated the association between genetic variants in two hepatic uptake transporter genes ( SLCO1B1 and SLC10A1 ) and the risk of anti-tuberculosis drug-induced hepatotoxicity (ATDH) in a Chinese cohort. The frequencies and distributions of single nucleotide polymorphisms (SNPs) and haplotypes of these genes were compared among 89 incident ATDH cases and 356 matched ATDH-free controls using a multivariate conditional logistic regression analysis. After correction for potential confounding factors, significant differences were found in polymorphism of rs4149014 under an addictive model ( P  = 0.008) and a recessive model ( P  = 0.016). The result of haplotype analysis suggested that patients carrying at least one SLCO1B1 *15 haplotype had a higher risk of ATDH (odds ratio (OR) = 1.74, 95% confidence intervals (CI): 1.04–2.90, P  = 0.034) in comparison with those carrying SLCO1B1 *1a or SLCO1B1 *1b haplotypes. These findings indicate that genetic variants of SLCO1B1 are associated with the development of ATDH in Chinese population.